Dampak Gaya Hidup Halal Dan Pemanfaatan Teknologi Informasi Terhadap Keputusan Generasi Z Dalam Menggunakan Layanan Bank Syariah - Tanjung, Defran (-, 2025)
This study aims to analyze the influence of halal lifestyle and information technology on Generation Z’s decision to utilize Islamic banking services among students of the Islamic Banking Study Program at Universitas Muhammadiyah Sumatera Utara (UMSU), both directly and indirectly. The research employs a quantitative approach. Partial analysis results indicate that the halal lifestyle has a significant influence on Generation Z’s decision, as evidenced by the calculated t value (2.588) being greater than the t table value (2.003) at a 5% significance level. Meanwhile, information technology also has a significant effect on Generation Z’s decision, with a calculated t value (4.467) exceeding the t table value (2.003). Based on the results of the simultaneous test (F-test), the calculated F value of 39.323 is greater than the F table value of 2.70, with a significance level of 0.001. These findings indicate that halal lifestyle and information technology together have a significant influence on Generation Z’s decision to use Islamic banking services. The Adjusted R Square value of 0.593 suggests that 59.3% of the variation in Generation Z’s decision is explained by these two variables.